Integrated approach for seed yield maximization in hybrid rice - Rajiv K. Singh; Pravin K. Upadhyay; S.S. Rathore; Kapila Shekhwat; Sandip K. Singh (Annals of Agricultural Research, 2023)
A field experiment was carried out at ICAR-Indian Institute of Seed Science, Kushmaur, Mau-275 103, Uttar Pradesh during kharif season (rainy) of 2014-15 to know the appropriate hybrid and fertilizer doses for maximization of seed yield in hybrid rice. The study was carried out in split plot design and replicated thrice. The experiment consisted of two hybrid rice, viz. DRRH-2 and DRRH3 in main plots and five fertilizer application in sub-plot, viz. Control, 100% RDF, 100% RDF+ ZnSO4 basal @ 25 kg/ha, 100% RDF+ZnSO4 foliar @ 0.5% and 100% RDF+ ZnSO4 basal @ 25 kg/ha + ZnSO4 foliar application @ 0.5%. Among two hybrid rice, DRRH-3 was significantly taller than the DRRH2 at various growth stages i.e., 30, 60, 90 DAT (days after transplanting) and at harvest (52.0, 84.0, 97.7 and 97.7 cm) as compared to DRRH-2. The among four doses of fertilizer, RDF + ZnSO4 basal + ZnSO4 foliar was showed higher response, which increases the plant height with increasing plant height at different stages i.e. 30, 60, 90 DAT and at harvest (55.6, 86.3, 99.9 cm) as compared to other doses and also over control. The present investigation also revealed that the hybrid DRRH-3 recorded higher panicle length (23.9 cm), seed/panicle (10.1), panicle weight (3.8g), test weight (18.7g), seed & straw yield (8.1 & 39.2q/ha), biological yield (47.3 q/ha) and harvest index (17.3) over DRRH-2. Among fertilizer doses, RDF + ZnSO4 basal + ZnSO4 foliar showed positive response, which increased all the yield and yield attributing characters viz., panicle length (24.5 cm), seed/panicle (10.9), panicle weight (5.2 g), test weight (20.0 g), seed yield (8.7 q/ha), straw yield (42.2 q/ha) and biological yield (50.9 q/ha) in both the hybrids compared to other fertilizer doses. DRRH-3 recorded significantly higher values for seed quality parameters viz., germination (93.3%), shoot length (13.7cm), seedling dry weight (0.829 g), vigour index-I & II (2549.6 & 78.2) over DRRH-2. Further fertilizer dose RDF + ZnSO4 basal + ZnSO4 foliar showed higher response for seed quality, germination (95.3%), shoot length (13.7 cm), seedling dry weight (0.89 g), vigour index-I & II (2622.9 & 85.7) as compared to other doses.